Mapping Shoreline Changes in the Situbondo Coastline for a Period of 10 Years Using Landsat 8 Satellite Image Data - Ary Candra Wibawa; Hendrata Wibisana (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
Coastal areas have the potential to prosper the surrounding community. The coastline is the boundary line between land and sea level that is dynamic. Changes in the coastline can lead to abrasion and accretion. This study aims to determine changes in the coastline on the Situbondo coast for a period of 10 years by taking Landsat 8 satellite image data processed using ArcGIS 10.7. The method used in this study uses the calculation of the Haversin formula and Euclidean Distance. The results showed that the smallest shoreline change in Situbondo Regency over a period of 10 years occurred in transect 24, precisely in Agel Village, Jangkar District with a shoreline change rate of 1.11 meters. While the largest 10-year shoreline change in Situbondo Regency occurred in transect 25, precisely in Kumbangsari Village, Jangkar District with a shoreline change rate of 106.42 meters.